Experimentation and cycle performance prediction of hybrid A/C system using automobile exhaust waste heat - Wang, Lei (2016)
A hybrid air-conditioning (A/C) system is proposed which consists of two cycles: (1) an ejector cycle driven by exhausted waste heat; and (2) a compressor A/C cycle. The system can operate under three modes: compressor, hybrid and ejector. Under the hybrid mode, the ejector driven by waste heat reduces the compression ratio (CR) of the compressor and boosts the compressor discharge pressure to the condenser pressure. The governing equations are derived based on energy and mass balances for each component of the system. The performance of the hybrid A/C system under compressor mode and hybrid mode is first analyzed theoretically at design conditions. Then it was tested experimentally through variations of (1) primary pressure from 11 to 23 bar; (2) evaporation pressure from 2.5 to 4.5 bar; and (3) condensation pressure from 9 to 12.5 bar, respectively. The experimental results show that the hybrid system is feasible, and can significantly enhance the performance of the automobile A/C systems, 35.2% COP improvement at the automobile idle conditions and more than 40% COP improvement when the automobile speeds over 80 km/h conditions. The increase of primary pressure and evaporation pressure has a positive effect on system performance while the increase of condensation pressure has a negative effect. The hybrid A/C system has the potential to be adopted in automobiles for the advantages of low cost, durable operation and better energy efficiency